Online MR guided dose escalated radiotherapy for organ preservation in distal rectal cancer. (November 2022) - Boeke, Simon; Uder, Laura; Ehlers, Jakob; Butzer, Sarah; Baumeister, Sabrina; Boldt, Jessica; Nachbar, Marcel; Lo Russo, Monica; Mönnich, David; Nikolaou, Konstantin; Zips, Daniel; Thorwarth, Daniela; et al.
Highlights: First series of MR-guided response adaptive dose escalated radiotherapy in rectal cancer. High patent acceptability with low acute toxicity and promising response rates. Abstract: Introduction: Non-surgical management of rectal cancer aiming for organ-preservation is an important development to improve rectal cancer treatment. Dose escalated radiotherapy represents one approach to increase clinical complete response (cCR) rates. In the present study we present feasibility and outcome data on rectal cancer patients who were treated with dose escalated radiotherapy using an MR guided online response-adaptive workflow. Material and methods: A total of five patients were treated with 45 Gy in 25 fractions to the mesorectum and the internal iliac lymph nodes and a simultaneous integrated boost to the primary tumor with 50 Gy in 25 fractions on a conventional linac. In addition, weekly response-adaptive boost fractions with 3 Gy per fraction were scheduled on a 1.5 T MR-Linac. Concomitant chemotherapy with 5-fluorouracil was given as continuous venous infusion during the first and last week of treatment. Response was evaluated approximately-three months after the end of treatment and surgery was omitted in case of a clinical complete response (cCR) or a near cCR. Toxicity was graded by using PRO-CTCAE, Quality of life by the EORTC-QLQ-C30 questionnaire and continence according to the Wexner scale. Results: Response-adaptive dose escalated radiotherapy was feasible and well tolerated by all patients. Four reached a clinical complete response, one had a local excision confirming pathological complete response (pCR). All PRO-CTCAE grade 3 toxicities resolved within six months after the end of treatment. Quality of life and continence scores during follow-up were comparable to baseline levels. Conclusion: Dose-escalated online response-adaptive MR-guided radiotherapy appears to be a very promising treatment with the goal of organ preservation in rectal cancer leading to high response rates, excellent organ function and limited side effects. Further prospective evaluation is needed.